Pixel clouds. Free photomodelling software for architectural survey. - Filippucci, Marco (DISEGNARECON, 2010)
Photomodelling refers to the innovative process in the digital environment, which transforms simple raster images into a three-dimensional model. The revolution of this technique is particularly explicit in a comparison of the cost of the instruments, the so inaccessible laser scanners on one hand, and the common digital cameras on the other hand. Furthermore, International research organizations have developed open source software that allows the creation of the numerical model and the elaboration of the point cloud. Based on personal research experiences and after on the teaching support, the aim of the study is to analyze the logic of these processes, to verify its applicability in the field of architectural research, making a useful way to understand the computer procedures and to determine criteria for evaluation of their reliability.